First Test and Characterizations on Urban Glass Waste with Waste-Derived Carbon Fiber Treated to Realize Foam Glass for Possible Construction Applications - Zakim Hussain; Seyed Mostafa Nouri; Matteo Sambucci; Marco Valente (Ceramics, 2025)
Urban glass waste is a significant by-product of residential areas, while scrap carbon fiber is a prevalent industrial by-product. This study explores an innovative approach to valorize these materials by producing foam glass (FG) for versatile applications, particularly in construction. A key challenge in FG production is enhancing its properties to meet increasingly stringent application-specific standards. The properties of FG are intrinsically linked to its porous structure, which depends on factors such as the foaming process. The oxidation of carbon fibers at high temperatures can induce a foaming effect, creating a porous matrix in the glass. This research investigates the effect of powdered recycled carbon fiber (PRCF)—an alternative method for recovering waste carbon fiber as a foaming agent for FG. PRCF was added at concentrations of 0.5%, 1%, and 1.5% by mass relative to powdered waste glass. Increasing PRCF content enhanced foaming and improved porosity, with total porosity rising from 47.18% at 0.5% PRCF to 65.54% at 1.5% PRCF, accompanied by a 50% reduction in compressive strength and a 68% decrease in thermal conductivity. The results demonstrate the feasibility of large-scale FG production with enhanced properties, achieved without substantial additional investment and by recovering two waste materials. This process supports sustainable development by promoting waste valorization and advancing circular economy principles.